‘Music in Film’ for gifted students: the effect of differentiated learning on students’ motivation - Ismail, Md Jais; Loo, Fung Chiat; Anuar, Azu Farhana (Universiti Putra Malaysia Press, 2021)
Music is not only an important subject in general education, but it particularly serves gifted students who face various psychological issues not encountered by their ‘normal’ peers. Nonetheless, it is found that not all schools are implementing proper music lessons due to the focus on STEM subjects. This paper provides an overview of developing music enrichment activities as an approach to meet gifted students’ needs. Differentiated instruction was used as the main approach to developing a comprehensive music enrichment activity, namely ‘Music in Film’, in which gifted students integrated music and computer skills in completing a given task. Furthermore, a research survey was conducted involving 36 gifted students. The MUSIC Inventory was used to measure their motivation and engagement towards the activity to measure the methods. Five domains empowerment, usefulness, success, interest and caring—were measured on a 6-point Likert scale. Results revealed that all five domains were rated from moderate to high by the gifted students with a minimum 4.5 mean. Although it can be concluded that this enrichment activity is apt and effective for implementation in gifted education, future studies could look at participants with different backgrounds and demographics. It is hoped that this paper will contribute to designing more enrichment activities with a differentiated instruction approach as gifted students possess high potential in various talents that need to be nurtured.